Sex Disparities in Colorectal Cancer Incidence by Anatomic Subsite, Race and Age - Murphy, Gwen (2010)
Though incidence of colorectal cancer (CRC) in the US, has declined in recent years, rates remain higher in men than women and the male-to-female incidence rate ratio (MF IRR) increases progressively across the colon from the cecum to the rectum. Rates among races/ethnicities other than Whites or Blacks have not been frequently reported. To examine CRC rates by sex across anatomic subsite, age, and racial/ethnic groups, we used the National Cancer Institute’s Surveillance, Epidemiology, and End Results (SEER) program for cases diagnosed among residents of 13 registries during 1992–2006. Incidence rates were expressed per 100,000 person-years and age-adjusted to the 2000 US Standard Population; MF IRR and 95% confidence intervals were also calculated. Among each racial/ethnic group, the MF IRR increased fairly monotonically from close to unity for cecal cancers to 1.81 (Hispanics) for rectal cancers. MF IRRs increased with age most rapidly for distal colon cancers from <1.0 at ages <50 years to 1.4–1.9 at older ages. The MF IRR for rectal cancers also rose with age from about 1.0 to 2.0. For proximal cancer, the MF IRR was consistently <1.5; among American Indian/Alaska Natives it was <1.0 across all ages. The MF IRRs for CRC vary markedly according to subsite and age but less by racial/ethnic group. These findings may partially reflect differences in screening experiences and access to medical care but also suggest that etiologic factors may be playing a role.